2012
DOI: 10.4103/0028-3886.93582
|View full text |Cite
|
Sign up to set email alerts
|

Atlantoaxial dislocation

Abstract: Atlanto-axial dislocations (AADs) may be classified into four varieties depending upon the direction and plane of the dislocation i.e. anteroposterior, rotatory, central, and mixed dislocations. However, from the surgical point of view these are divided into two categories i.e. reducible (RAADs) and irreducible (IAADs). Posterior fusion is the treatment of choice for RAAD. Transarticular screw fixation with sub-laminar wiring is the most stable& method of posterior fusion. Often, IAAD is due to inadequate exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 22 publications
1
38
0
1
Order By: Relevance
“…Tucker and Taylor12 have shown that in these circumstances the area of the space enclosed by the atlas reduces to 36%, which is just sufficient to avoid cord compromise. In our patient, and in other cases described in the literature, the neurological deficit is consequently mild 3 4 10. The exception to this is the case described by Chaudhary et al where the patient suffered a hyperextension injury followed by hyperflexion.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Tucker and Taylor12 have shown that in these circumstances the area of the space enclosed by the atlas reduces to 36%, which is just sufficient to avoid cord compromise. In our patient, and in other cases described in the literature, the neurological deficit is consequently mild 3 4 10. The exception to this is the case described by Chaudhary et al where the patient suffered a hyperextension injury followed by hyperflexion.…”
Section: Discussionsupporting
confidence: 72%
“…It was felt in these patients that the transverse ligament was partially intact, conferring some stability 2. In two cases, there was persistent instability requiring delayed posterior fusion of C1-C2 3 8. In all other cases, open reduction and fixation were required.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The main characteristic of incongruence is represented by the disruption of this relationship, which was assessed in this study in CT multiplanar images of all affected patients. The combined diagnostic approach described herein, which included both CT and MRI, is consistent with the described approach recently described in veterinary research and used in human medicine for complete evaluation of the cranio-spinal junction [8,14,16,25].…”
Section: Discussionmentioning
confidence: 88%